PENGARUH KREDIT YANG DISALURKAN PADA HUBUNGAN ANTARA DANA PIHAK KETIGA DENGAN PROFITABILITAS - Trisnawati, Ni Nyoman Ayu Adelina; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2015)
Denpasar City has 4 Districts with 35 LPD scattered throughout the Village in the city of Denpasar. LPD has an role in supporting the development of the Village People. Inconsistency of some of the results of previous studies on the effect of third-party funds on profitability, it is important to add in lending as a moderating variable. This study aims to determine the effect of outstanding loans on the relationship between the DPK with profitability. Method of determining the sample in this study is done by using sampling techniques saturated, using the entire LPD in Denpasar listed in LPLPD city of Denpasar. The sample consisted of 105 observations. This study tested using regression analysis moderation with SPSS 15:00  For Windows. F rom results  of the analysis can be concluded that DPK variable has no effect on profitability, while outstanding loans can be moderate to strengthen the influence of deposits in profitability.
Keywords: Third Party Funds, Loans to Deposit Ratio (LDR), Profitability